Duas professoras de espanhol língua estrangeira (ele) e suas (des)crenças sobre o livro didático - Vieira, Ana Nelcinda Garcia (2016)
When the foreign language teacher is planning classes and creating didactic material, he/she must bear in mind certain factors, such as an analysis of students` needs, their interaction, the use of authentic materials, linguistic autonomy focusing the sociocultural context, among some others (GELABERT et al., 2002). These conditions also appear in the legal orientations that guide the teaching of a Foreign Language in Brazil. As a way of teacher`s support in Brazil, the National Program of Textbook (PNLD) distributes textbooks to public elementary and high schools, among which, Spanish language textbooks. This research aims to analyze the relation between teacher`s work and the textbook, through the beliefs of two teachers of Spanish as a Foreign Language of public schools in a city of Rio Grande do Sul. To do so, the contexts of two schools were described and after that, the beliefs of the two teachers were analyzed and also the way that these beliefs influence their actions. This is a qualitative research, based on the study of beliefs in learning, according to Barcelos (2000, 2001, 2004, 2010) and Silva (2007, 2011), with an emphasis on the contextual approach of beliefs. The theoretical support of this analysis also includes: the production of didactic material for Foreign Language teaching, according to Leffa (2003), Gelabert et al. (2002), García (2011) and Ferro and Bergmann (2008); the formation of the Foreign Language teacher, according to Coracini (1999), Celani (2001) and Leffa (2001); the teaching approaches according to Misukami (1986); and the teacher`s role under the perspective of Kumaravadivelu (2008). For the collection of the data, semi structured interviews were carried out with the teachers and also talks were held with the school principals and pedagogic coordinators, besides secondary data sources, such as the Political Pedagogical Projects of the schools, students`s notebooks, the National Curricular Parameters (PCNs) and the Curricular Orientations for the High School (OCEM). Results indicate that the beliefs of the participating teachers are diverse, what guides and determines different actions relating the didactic material, especially their attitude towards the textbook, reflecting in the way the teachers act in their respective contexts. Thus, while one of them uses the didactic material in a traditional way, textbook centered, aiming to teach how to translate texts, the other teacher produces her Didactic Material and uses it in an interactive way, aiming to contribute to form a student who will be prepared to act in different situations and also to reflect and discuss about many topics. Also, despite the geographical proximity of the schools, the contexts are socially distant.